1975
DOI: 10.1530/jrf.0.0430057
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone, Oestrogen and Progesterone Levels in Peripheral Serum of Anoestrous and Cyclic Ewes as Determined by Radioimmunoassay

Abstract: Summary. Jugular vein blood was collected daily from four mature ewes throughout anoestrus and the first oestrous cycle of the breeding season until 4 days after the second oestrus. The levels of oestrogen, progesterone and LH were determined by radioimmunoassay. There were fluctuations in the LH level throughout most of the observed anoestrous period with a mean \ m=+-\ S.E. value of 2\m=.\3\ m=+-\ 0\m=.\9 ng/ml. High LH values of 20\m=.\0, 41\m=.\2and 137\m=.\5 ng/ml were observed in three ewes on Day \m=-\2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
1
1

Year Published

1977
1977
1992
1992

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 27 publications
10
36
1
1
Order By: Relevance
“…The progesterone concentrations of Ewes 1, 3 and 4 were <0·5 ng/ml at all times during anoestrus but the level of 0-38 ng/ml in the first sample collected from Ewe 2 on Day -9 had increased to 1 -32 ng/ml by the end of the 24-h collection period, perhaps indicating that luteinization had begun. These data lend further support to previous findings that episodic releases of LH occur in the anoestrous ewe (Cicmanec & Niswender, 1973;Akbar et al, 1974;Yuthasastrakosol et al, 1975). Foster et al (1975) also observed pulsatile releases of LH in ewe lambs as they approach sexual maturity, but like us, they were unable to detect any marked change in the release pattern or peak amplitude before the first ovulation at puberty.…”
Section: Resultssupporting
confidence: 91%
“…The progesterone concentrations of Ewes 1, 3 and 4 were <0·5 ng/ml at all times during anoestrus but the level of 0-38 ng/ml in the first sample collected from Ewe 2 on Day -9 had increased to 1 -32 ng/ml by the end of the 24-h collection period, perhaps indicating that luteinization had begun. These data lend further support to previous findings that episodic releases of LH occur in the anoestrous ewe (Cicmanec & Niswender, 1973;Akbar et al, 1974;Yuthasastrakosol et al, 1975). Foster et al (1975) also observed pulsatile releases of LH in ewe lambs as they approach sexual maturity, but like us, they were unable to detect any marked change in the release pattern or peak amplitude before the first ovulation at puberty.…”
Section: Resultssupporting
confidence: 91%
“…These results support previous demonstrations that brief increments in progesterone occur just before the first full-length luteal phase of the breeding season (Yuthasastrakosol et al, 1975;Walton et ai, 1977). In addition, the present results demonstrate that one or more of these brief rises in progesterone can occur within 1-4 weeks before the first full-length luteal phase, the same time interval as the previously-defined transition period, during which one or more increases in LH pulse frequency were observed.…”
Section: Methodssupporting
confidence: 92%
“…Short-lived corpora lutea are observed after the first ovulation after parturition in cows (Lamming et al, 1981;Humphrey et al, 1983) and sheep (Wise et al, 1986) and after the first ovulation of the breeding season in sheep (Yuthasastrakosol et al, 1975;Walton et al, 1977). Additionally, the first ovulation at puberty in heifers (González-Padilla et al, 1975), ewes (Berardinelli et al, 1980) and primates (Young & Yerkes, 1943;Wentz, 1979;Resko et al, 1982) is frequently followed by a short luteal phase.…”
Section: Introductionmentioning
confidence: 99%